Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Permainan Bola Bekel Di TK IT Shepita Meliani - Shepita Meliani; Melvi Lesmana Alim; Yenda Puspita; Musnar Indra Daulay; Joni Joni (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to improve the fine motor skills of early childhood through the activity of playing bekel ball at TK IT Tahfidz Insan Madani. The background of this research is based on the low fine motor skills of children, as seen from the suboptimal coordination of eye and hand movements, finger flexibility, and dexterity in writing and playing activities. The method used is Classroom Action Research (CAR) based on the Arikunto model, carried out in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 20 children aged 5-6 years at TK IT Tahfidz Insan Madani. Data were collected through observation, interviews, documentation, and children's development assessment sheets. The results showed a significant improvement in children’s fine motor skills after implementing the bekel ball game activity. In the pre-action stage, the percentage of children in the Very Well Developed (BSB) category was only 5%. After the first cycle, it increased to 35%, and in the second cycle, it reached 80%. The bekel ball game proved to be effective in enhancing eye-hand coordination, finger dexterity, and children's agility in carrying out fine motor activities. Thus, it can be concluded that the bekel ball game activity can be an effective and enjoyable alternative learning medium to improve the fine motor skills of early childhood at TK IT Tahfidz Insan Madani